Profiling the market of German customer for South Karelia Region - Kivelä, Marjukka (Saimaan ammattikorkeakoulu, 2011)
ABSTRACT Germany as a country has enough people to travel also to Finland. The task is to find the right channels for it. The business culture of Germany is promising good relationships because the cultures are facing well each others. The statistics shows the changes during the years and the number of people who travel to Finland is growing. South Karelia would need new innovations to enhance visibility among other places in Finland. A distribution channel by Kalakota and Robinson is connecting all the business actions. Keeping contact with the consumers is important because the money that you are spending to get a new customer is higher than amount of money keeping existing ones. Distribution channels to the tourism industry are extremely vital, even more vital than in other trade industries due to the fast changes in the field. The Internet has impact and is impacting the tourism industry in a hard way, companies must be available online. The consumers are demanding, but the consumers are also them which behaviour is interesting companies the most. The needs and desires of the consumer must be known before the product or service is produced to the public. The main aim of this thesis is to get to launched the tourism profile of German market, to know how the customers are behaving, what they are looking for when travelling to South Karelia, and to know ways of distributing the information and which channels are the important ones. The results of the research show that nature and quietness of South Karelia attracts the Germans. The Internet is the way how consumers are finding the companies and the companies are finding the new resorts by touring in Finland and using the help of hotel chains and national tourist offices.